The influence of the use of crossword puzzle on the vocabulary mastery among the second semester students of the English Education Department of Muhammadiyah University Metro - Anggraini, Reni; Faliyanti, Eva; Kusumawati, Fitri Palupi (Universitas Ahmad Dahlan, 2022)
This study aims to find out the influence of crossword puzzles on vocabulary mastery among the second semester students of the English Education Department of Muhammadiyah University Metro. The design of this research is experimental, which means that the research method requires two variables to compare the influencing factors. The data were quantitative in nature. Data collection was performed through the implementation of pre-test and post-test. The research chose the second semester students of the English Education Department of Muhammadiyah University Metro as the population. The students were divided into two groups, namely experimental and control groups. The experimental group consisted of 16 students. The data were collected with the implementation of pre-test and post-test as the instruments. The data analysis showed that the mean score of the post-test was higher than that of the pre-test (85.12 > 50.50). It showed that the t ratio was higher than t table (16.651 > 2.131) and the sig. 2 tailed was lower than sig. level (0.000 < 0.05). Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that the use of crossword puzzles influences students' vocabulary mastery.